Investigating the psychometric properties of the social exposure to nonsuicidal self-injury scale in students - Ali Sheykholreslami; Nastaran Seyedesmaili Ghomi; Ali Salmani; Aysan Sharei (مطالعات روانشناسی تربیتی)
The present study was conducted with the aim of investigating the psychometric properties of the Social Exposure to Nonsuicidal Self-Injury Scale in students. The present research method was descriptive and of the type of psychometric studies. The statistical population of the present study was formed by all the students of the second secondary school in Ardabil city in the academic year of 2023-2024. From this population, a sample size of 200 people was selected by cluster random sampling method and to questionnaires on Social Exposure to Nonsuicidal Self-Injury, Zelkowitz and Cole (2017), Neff et al.'s (2003) self-compassion questionnaire and Non-Suicidal Self-Injury expectancies Questionnaire Hosking and Boyes (2017) responded. Internal consistency coefficient, concurrent validity, exploratory and confirmatory factor analysis were used for data analysis. Data were analyzed using SPSS26 and Amos24 software. The results of the internal consistency coefficient showed that this scale has good reliability (α=0.83). The results of the correlation coefficient showed that the positive correlation between two variables in the Social Exposure to Nonsuicidal Self-Injury with Non-Suicidal Self-Injury expectancies (r=0.27, P<0.001) indicates appropriate convergent validity and the negative correlation coefficient between the two variables in the Social Exposure to Nonsuicidal Self-Injury with Self-Compassion (r=-0.25, P<0.001) indicates adequate divergent validity. The fit indices of the confirmatory factor analysis model also confirmed the final model of this scale. The results of this research showed that the Persian version of the Social Exposure to Nonsuicidal Self-Injury Scale intent has good reliability and validity in the Iranian population and is a suitable self-assessment scale for clinical and research situations.